NETRALITAS KEPOLISIAN REPUBLIK INDONESIA PADA PEMILIHAN UMUM (PEMILU) - La Ode Abdul, Hamid; Anugerah, Wahid (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This research is a type of normative juridical research using a statutory approach, a conceptual approach. This research was conducted to determine: 1) How is the neutrality of the Indonesian police in the election? 2) What are the obstacles to the neutrality of the Indonesian police in the election? The results of the research are that the neutrality of the Indonesian police reflects its ability to carry out state duties without siding with certain political interests. The Indonesian police have a crucial role in ensuring security, order, and justice during the election, including securing polling locations, enforcing the law against election violations, and providing a sense of security to the community. However, maintaining the neutrality of the Indonesian police is not an easy task. The Indonesian police are faced with various challenges, such as political pressure, intervention of political interests, and the need for political parties to maintain the neutrality of the Indonesian police. and threats to the security of its personnel. Nevertheless, the Indonesian National Police (Polri) has developed various strategies to address these challenges and maintain its neutrality during the election. A further problem is the continued involvement of the police in the election due to the political interests of certain groups.